Quality of life and outcome of patients with metastatic pancreatic cancer receiving first-line chemotherapy with nab-paclitaxel and gemcitabine: real-life results from the prospective QOLIXANE trial of the Platform for Outcome, Quality of Life and Translational Research on Pancreatic Cancer registry - Batran, Salah-Eddin al-; Hofheinz, Ralf-Dieter; Reichart, Alexander; Pauligk, Claudia; Schönherr, Caroline; Schlag, Rudolf; Siegler, Gabriele; Dörfel, Steffen; Koenigsmann, Michael; Zahn, Mark-Oliver; Schubert, Jörg; Aldaoud, Ali; et al. (International journal of cancer, 2021)
Few data exist on health-related quality of life (QoL) in patients with metastatic pancreatic cancer (mPC) receiving first-line chemotherapy (Awad L ZE, Mesbah M Boston, MA. Applying survival data methodology to analyze quality of life data, in Mesbah M, Cole BF, Ting Lee M-L (eds): Statistical Methods for Quality of Life Studies: Design, Measurements and Analysis. Kluwer Academic Publishers 2002). The QOLIXANE study is a prospective, noninterventional, multicenter substudy of the Platform for Outcome, Quality of Life and Translational Research on Pancreatic Cancer (PARAGON) registry, which evaluated QoL in patients with mPC receiving first-line gemcitabine and nab-paclitaxel chemotherapy in real-life setting. QoL was prospectively measured via EORTC QLQ-C30 questionnaires at baseline and every month thereafter. Therapy and efficacy parameters were prospectively collected. Main objectives were the rate of patients without deterioration of Global Health Status/QoL (GHS/QoL) at 3 and 6 months. Six hundred patients were enrolled in 95 German study sites. Median progression-free survival was 5.9 months (95% confidence interval [CI], 5.2-6.3). Median overall survival (OS) was 8.9 months (95% CI, 7.9-10.2), while median time to deterioration of GHS/QoL was 4.7 months (95% CI, 4.0-5.6). With a baseline GHS/QoL score of 46 (SD, 22.8), baseline QoL of the patients was severely impaired, in most cases due to loss in role functioning and fatigue. In the Kaplan-Meier analysis, 61% and 41% of patients had maintained GHS/QoL after 3 and 6 months, respectively. However, in the QoL response analysis, 35% and 19% of patients had maintained (improved or stable) GHS/QoL after 3 and 6 months, respectively, while 14% and 9% had deteriorated GHS/QoL with the remaining patients being nonevaluable. In the Cox regression analysis, GHS/QoL scores strongly predicted survival with a hazard ratio of 0.86 (P < .0001). Patients with mPC have poor QoL at baseline that deteriorates within a median of 4.7 months. Treatment with gemcitabine and nab-paclitaxel is associated with maintained QoL in relevant proportions of patients. However, overall, results remain poor, reflecting the aggressive nature of the disease.